A Novel BD2-Selective Inhibitor of BRDs Mitigates ROS Production and OA Pathogenesis - Hyemi Lee; Jihye Choe; Min-Hee Son; In-Hyun Lee; Min Ju Lim; Jimin Jeon; Siyoung Yang (MDPI AG, 2024)
Bromodomain and extra-terminal domain (BET) family proteins regulate transcription and recognize lysine residues in histones. Selective BET inhibitors targeting one domain have attracted attention because they maintain normal physiological activities, whereas pan (nonselective) BET inhibitors do not. Osteoarthritis (OA) is a joint disorder characterized by cartilage degeneration for which no treatment currently exists. Here, we investigated whether the selective inhibition of BET proteins is an appropriate therapeutic strategy for OA. We focused on the development and characterization of 2-(4-(2-(dimethylamino)ethoxy)-3,5-dimethylphenyl)-5,7-dimethoxyquinazolin-4(3H)-one (BBC0906), a novel bromodomain 2 (BD2)-specific inhibitor designed to suppress OA progression. Using a DNA-encoded chemical library (DEL) screening approach, BBC0906 was identified because of its high affinity with the BD2 domain of BET proteins. BBC0906 effectively reduced reactive oxygen species (ROS) production and suppressed catabolic factor expression in chondrocytes in vitro. Moreover, in an OA mouse model induced by the destabilization of the medial meniscus (DMM), BBC0906 intra-articular injection attenuated cartilage degradation and alleviated OA. Importantly, BBC0906 selectively inhibits the BD2 domain, thus minimizing its potential side effects. We highlighted the therapeutic potential of targeting BET proteins to modulate oxidative stress and suppress cartilage degradation in OA. BBC0906 is a promising candidate for OA treatment, offering improved safety and efficacy.